Examining 'colocalization': succession, segregation and Contestation of foreign workers and local residents within the Urban and peri-urban areas of Penang, Malaysia. - Ghazali, Suriati (Universiti Sains Malaysia, 2014)

(untitled)
Studies on colocalization of industry firms and the benefits it derived to diversified economic regions have been made by nany. However, the issues on colocalization - or coexistence and integration - of foreign workers with local residents in diversified economic regions, is less studied, particularly in Malaysia. This research poses question on the extent to which foreign workers in Malaysia integrate with local residents; and factors that encourage integration between them. The objective is to investigate the coexistence and integration of foreign workers with local residents, and their positive contributions to social, economic and cultural development. Residential areas in urban and peri-urban Penang were chosen as study sites. 108 local residents and 109 foreign workers were selected for a questionnaire survey, and 30 involved in detailed study. Respondents were chosen using stratified random, purposive and convenient sampling. Respondents of local residents were Malaysian Malay, Chinese and Indian, meanwhile respondents for foreign workers involved IndoneSians, Bangladeshis, Nepalese, Burmese, Vietnamese, Pakistanis, etc. Frequency data was tabulated; jowever the understanding of colocalization patterns and processes were only achieved using qualitative information that were gathered from detailed, informal interviews and participant observation.There are 'silent' segregation, contestation and competition among the two groups. Genuine social integration between them is difficult to achieve, however, a relatively straightforward integration is evident between nationals that share similar social and cultural ylements, such as belief and language. Belief or language led to similarities in everyday behavior, attitude and perception, thus promote better social interaction amongst them. Therefore such similarities offer the opportunities for integration, which advanced to healthy economic, social and cultural landscapes in urban and peri-urban regions of Penang, Malaysia.